New data on the genus Urophonius in Patagonia with a description of a new species of the exochus group (Scorpiones: Bothriuridae) - Ojanguren Affilastro, Andres Alejandro (2009)
New data on the distribution and systematics of Patagonian species of the scorpion genus Urophonius Pocock 1893 are provided. A species of this genus from Pennsula Valds in central eastern Argentinean Patagonia, Urophonius martinezi new species, is described. The surface activity period of most of the species of the genus is reviewed and clearly established. A distribution map as well as a key for the Patagonian species of the genus are provided.